Choice determinants of the mobility in the Dutch health insurance market - Mosca, Ilaria (Springer-Verlag, 2007)
We estimate a Logit model for the choice determinants of the mobility in the Dutch market for health insurance in 2006. The results highlight that socio-economic, geographical, and health-related factors matter in the decision to switch health care insurer. Moreover, previous contact with the insurer and the former type of health policy are also of influence.